Tapatybės vardan: tarpkultūrinio supratimo mokymas tarpkultūrinėje klasėje - Meyer, Ulrike (Information & Media, 2008)
Būti grupės nariu – ar kultūrinės, religinės ar tautos – ką tai reiškia? kodėl mes norime būti tam tikros bendruomenės nariai, nors tai dažnai susiję su kitų baime ar agresija? kas tai – tapatybė?Amin Maalouf, libanietis, krikščionis, rašantis prancūziškai, dėl savo prigimties turi daugelį tapatybių. Toks pavyzdys rodo, kad bendras „tapatybės“ suvokimas yra netinkamas ir netgi pavojingas. Toks pavyzdys atskleidžia, kad tapatybė negali būti stabili, ir ji apibrėžiama atsižvelgiant į priklausymą grupei.Šiame straipsnyje siekiama parodyti, kaip metodas “Examen d’identité” gali būti taikomas auditorijoje ir kurio rezultatai gali būti lyginami ir aptariami studentams įvardijus tapatybės elementus ir atitikimą.In the name of identity: Teaching cultural awareness in the intercultural classroomUlrike MeyerSummaryBeing part of a group – be it a cultural, religious or national one – what does it mean? Why do we want to be part of a community, although this very often leads to fear of others and to all kinds of aggression? “Identity” – what is this?Amin Maalouf, Lebanese by birth, Christian by religion, writing in French and from a position of multiple identities (“I am posed between two countries, two or three languages, and several cultural traditions”), tries to show that the common notion of “identity” is false – and dangerous. He shows that identity is not stable and defined by belonging to one group or another. He suggests a way that might help accepting a multiplicity of equally legitimate allegiances. Maalouf’s “identity check-up” is an effective way for analysing one’s own identity and has proven to be useful in culturally mixed classes as a basis for self-analysis and discussion. Many students in countries like Germany, with a high number of immigrants, have experienced the influence of different cultures, religions, societies and are open for a notion of “identity” as a kind of a dynamic puzzle.The paper will show how this “examen d’identité” can be used in the classroom and compare and discuss the results of these identity check-ups, filled-in by the students.Key words: identity, cultural identity, self-analysis, intercultural communication, international classroom, pedagogical approach